2022
DOI: 10.1001/jamapediatrics.2022.1174
|View full text |Cite
|
Sign up to set email alerts
|

Race, Overdose Deaths, and Years of Lost Life—Reply

Abstract: To the Editor In their study of fatal drug overdoses among young people aged 10 to 24 years, Hall and colleagues 1 report 21 689 deaths from 2015 to 2019, which resulted in 1.23 million years of lost life (YLL). This averages to 57 YLL per overdose death, a devastating statistic.The authors' life expectancy data source, the Social Security Administration Period Life Table, did not include information on race; therefore, race-specific YLLs were not provided. However, we can be reasonably sure that the burden of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In contrast to the fear of being shamed and judged by traditional health care providers, 10 the participants and PRC were able to connect through their shared experiences and develop a trusting relationship. Literature suggests that traditional health providers tend to less proactively address the many social and structural determinants of health and/or provide passive referrals, 12 whereas CARE PRC embraced these as part of their primary roles.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast to the fear of being shamed and judged by traditional health care providers, 10 the participants and PRC were able to connect through their shared experiences and develop a trusting relationship. Literature suggests that traditional health providers tend to less proactively address the many social and structural determinants of health and/or provide passive referrals, 12 whereas CARE PRC embraced these as part of their primary roles.…”
Section: Discussionmentioning
confidence: 93%
“…Participants reported that they would be more likely to seek treatment earlier and adhere to treatment recommendations if they had not feared discrimination from the medical personnel. 10 Treatment motivation and the perceived need for treatment for SUD are also culturally different among patient populations. 9,11 In addition to discussing barriers to SUD treatment, assessing factors that influence retention are just as essential to improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation